Applying circular economy principles in the oil & gas industry - An LCA study of the decommissioning process of offshore platforms - Terpou, Aikaterini (My University, 2017)
Many offshore platforms are soon to reach or have already reached their mature phase, which means that in the foreseeable future, measures will need to be taken for their eventual removal. After their decommissioning, these platforms are a potential source of huge amounts of materials. The current study aimed to investigate how the oil & gas industry can improve its environmental performance by implementing the Circular Economy principles during the decommissioning process. More concretely, it was hypothesized that the environmental performance of the system would change if reuse was involved in the final stages of decommissioning. For these purposes, the Life Cycle Assessment procedure was implemented. The results show that partial decommissioning is a better option than complete decommissioning due to lower energy use during recycling and transportation. The results of a reuse scenario suggest that the environmental impacts of both decommissioning methods are reduced. Sensitivity analysis indicated that when the percentage of reuse is increased, the performances of complete and partial decommissioning from an environmental perspective both improve. This thesis concludes that optimising marine vessels used for transporting a platform’s pieces could help reduce emissions from that particular process. At the same time, reducing the amount of material that goes to recycling by increasing the reuse of certain assets of the platform, would improve the environmental performance of these decommissioning stages. It was also identified that there is a need for data transparency in the decommissioning field in order to produce more certain and accurate results.
Keywords: Annan naturvetenskap; Other Natural Sciences